ANALISIS BIAYA DAN KESESUAIAN PENGGUNAAN ANTIBIOTIKA PADA DEMAM TIFOID DI RSUD KOTA YOGYKARTA - , Ria Etikasari, S. F., Apt, Prof. dr. Ali Gufron Mukti, M.Sc., P.hD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The appropriateness of choosing antibiotics to treat typhoid fever decreases the cost of care affectively. The objectives of the research are to describe theraphy of typhoid fever, to describe the appropriatness of choosing antibiotic, to describe the total hospitalizing cost of typhoid fever, and to describe the appropriatness of the Jamkesmas patientâs cost of illness and the INA CBGs. The data of the descriptive analytical research are medical records of patients who were hospitalized in Regional General Hospital of Yogyakarta on 1 st October, 2009 up to 31 st September, 2011. The researcher observes the patientâs recipes to analyze the use of antibiotics. The patientâs invoices are analyzed to calculate the total hospitalizing cost of typhoid fever considering the influencing factors (T-Test, Oneway Anova and Kruskal Wallis test with the trustworthy level of 95%) and the cost of hospitalizing and the length of stay are compared to INA CBGs by One Sample T-Test. Of the 86 patients as the respondent there are 50 males. Most are 6 â 12 years old (35%). Among four catagories most patients are categorized as general patient (41.86%). Most of typhoid fever patients (60.47% of the all subjects) were hospitalized in third-level rooms. Most of typhoid fever patients (44.18%) were hospitalized for 5 â 10 days. The appropriateness of antibiotics use of childhood patients is 91.86% and the appropriateness of antibiotic use of adult patients is 100%. The cost rate of care of typhoid fever patients in VIP rooms is Rp. 3,076,700.78. The total cost rate of care of Askes Sosial sevice is Rp. 2,698,632.20. Factors that influencing on the cost rate are age (P = .013), length of stay (P = .001), class of service (P = .000) and kinds of medical service (P = .002). The total cost of care and length of stay of Jamkesmas patients agree with the INA CBGs.